Development of indirect competitive enzyme-linked immunosorbent and immunochromatographic strip assays for carbofuran detection in fruits and vegetables. Issue 4 (4th July 2017) - Yao, Leijun; Liu, Liqiang; Song, Shanshan; Kuang, Hua; Xu, Chuanlai
ABSTRACT: Carbofuran is a highly toxic pesticide used in fruits and vegetables. In this study, we produced a specific and sensitive monoclonal antibody (mAb) which was prepared based on a hapten that was derivatized with benzofuranol against carbofuran. Following mice immunization and cell fusion, we obtained three monoclonal cell lines: 6D5, 3H2, and 3C6. The cell line 3H2 generated mAb with the highest affinity and sensitivity. The half maximal inhibitory concentration was 0.3 ng/mL, and the cross-reactivity was <1%. Based on this mAb, an indirect competitive enzyme-linked immunosorbent assay (ic-ELISA) and immunochromatographic test strip (ICS) assay were developed to detect carbofuran residues in cucumbers and apples. The working range of ic-ELISA was 0.1–1 ng/mL, and the cutoff value of ICS was 1 ng/mL. The analytical recovery of carbofuran in cucumber and apple samples ranged from 81% to 97%. Both methods represent rapid screening tools for carbofuran detection in fruits and vegetables.